2018
DOI: 10.4103/sni.sni_64_18
|View full text |Cite
|
Sign up to set email alerts
|

Abscess due to textiloma (gossypiboma: Retained surgical cottonoid)

Abstract: Background:Surgical site infections following spinal surgery, including spinal abscesses, are rare but serious as they are major causes of morbidity, and even mortality. They are, however, rarely attributed to infected, retained surgical cottonoids or sponges (textiloma or gossypiboma) inadvertently left in an operative field.Case Description:A 53-year-old female with a history of two prior spinal operations at the L4-S1 levels (11 and 2 years previously) presented over a few weeks with the acute onset of a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Important risk factors predisposing to the occurrence of textiloma include emergency surgical intervention, complex and protracted surgeries, change in surgical approach during the procedure, surplus blood loss necessitating the use of a larger number of sponges, inaccuracies in pre-and post-surgical sponge counts and a greater body-mass-index of the patient (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Important risk factors predisposing to the occurrence of textiloma include emergency surgical intervention, complex and protracted surgeries, change in surgical approach during the procedure, surplus blood loss necessitating the use of a larger number of sponges, inaccuracies in pre-and post-surgical sponge counts and a greater body-mass-index of the patient (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…[15] Indeed, CES diagnosis often becomes a mounting medicolegal issue with at least one study documenting that in 96% of cases of CES brought to a malpractice insurance organization, 65% progressed to claims by the affected patients, and 48% of these cases resulted in payment of compensation for damages. [34] It must be noted that rare cases of CES resulting from iatrogenic causes such as retained surgical cottonoids,[4] epidural steroid injections,[10] and even a pathological engorgement of the epidural venous plexus after elective lumbar microdiscectomy[32] have been reported in literature with additional consequences. Furthermore, studies have shown that a delay in treatment typically results in adverse legal decision highlighting the requisite expedited intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Le terme Textilome signifie la présence d'une réaction inflammatoire induite par un corps textile au contact des tissus. C'est une complication post opératoire rare et ubiquitaire dans l'organisme [2]. Son incidence varie de 0.001 à 0.01%.…”
Section: Discussionunclassified